Blender 2.49 scripting : extend the power and flexibility of Blender with the help of Python: a high-level, easy-to-learn scripting language /: extend the power and flexibility of Blender with the help of Python: a high-level, easy-to-learn scripting language. (2010) - Unknown
No abstract available